Protocol for preparing cellulose-based aerogels in a deep eutectic solvent as surface-enhanced Raman scattering substrates - Kaori Sánchez-Carrillo; Sandeep Surendra Panikar; Josué D. Mota-Morales (STAR Protocols)
Summary: There is an increasing need to detect and identify analytes of diverse origins in low molar concentrations and from complex matrices. Here, we introduce a protocol for preparing surface-enhanced Raman scattering (SERS) substrates that enable the detection of aqueous analytes in ultralow concentrations. We describe the procedure for synthesizing plasmonic aerogels using L-ascorbic acid as a reductor and eutectic solvents as reaction media. We then detail procedures for measurements using these substrates.For complete details on the use and execution of this protocol, please refer to Panikar et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.